Static potential in QED(3) with nonminimal coupling - Dalmazi, D. (American Physical Soc, 2004)
Here we study the effect of the nonminimal coupling j(mu)epsilon(munualpha)partial derivative(nu)A(alpha) on the static potential in multiflavor QED(3). Both cases of four and two components fermions are studied separately at leading order in the 1/N expansion. Although a nonlocal Chern-Simons term appears, in the four components case the photon is still massless leading to a confining logarithmic potential similar to the classical one. In the two components case, as expected, the parity breaking fermion mass term generates a traditional Chern-Simons term which makes the photon massive and we have a screening potential which vanishes at large intercharge distance. The extra nonminimal couplings have no important influence on the static potential at large intercharge distances. However, interesting effects show up at finite distances. In particular, for strong enough nonminimal coupling we may have a new massive pole in the photon propagator, while in the opposite limit there may be no poles at all in the irreducible case. We also found that, in general, the nonminimal couplings lead to a finite range repulsive force between charges of opposite signs.